Cardiac event risk stratification in patients with end-stage renal disease: Sub-analysis of the B-SAFE study. (1st January 2016) - Zen, Kan; Tamaki, Nagara; Nishimura, Masato; Nakatani, Eiji; Moroi, Masao; Nishimura, Tsunehiko; Hasebe, Naoyuki; Kikuchi, Kenjiro
Abstract: Background: The aim of this study was to investigate whether 123I-labelled β-methyl iodophenyl–pentadecanoic acid (BMIPP) imaging as an abnormal myocardial fatty acid metabolism indicator better predicted fatal and non-fatal cardiac events than conventional predictors [e.g. peripheral artery disease (PAD) and diabetes mellitus (DM)] in haemodialysis patients. Methods: In a sub-analysis of the BMIPP SPECT Analysis for Decreasing Cardiac Events in Haemodialysis Patients (B-SAFE) study, 677 asymptomatic patients with ≥ 1 cardiovascular risk factor and without known coronary artery disease were followed for 3 years. The amount of radioactivity in each 17-left ventricular segment was graded visually and assigned a score from 0 (normal) to 4 (absent). Its total values were designated as baseline summed BMIPP scores. Outcome measures were composite cardiac events. Results: Cardiac events correlated with age, PAD [hazard ratio (HR): 2.15; p = 0.003], DM (HR: 1.76; p = 0.006) and summed BMIPP scores (4–8, HR: 1.82; p < 0.001; ≥ 9, HR: 3.49; p < 0.001). Cardiac event-free rates decreased with increasing summed BMIPP scores, PAD and DM. Areas under the receiver operating curves (AUCs) indicated that a BMIPP-based model (AUC: 0.656) was more predictive than DM or PAD models (AUC: 0.591); a model with all three was most predictive (AUC: 0.708). The three-year cardiac event-free rates significantly decreased in patients with PAD and/or DM in all summed BMIPP score categories. Conclusions: Abnormal myocardial fatty acid metabolism strongly predicts cardiac events in haemodialysis patients; those with PAD or DM are at high risk for cardiac events.